In and Beyond the Faith: Religion as a Determinant of Women’s Civic Activity. A Case of Women’s Protest Against the Tightening of Abortion Law - Tomczyk, Justyna (Przegląd Badań Edukacyjnych (Educational Studies Review), 2023)
This article is based on empirical research conducted as part of a wider research project on active citizenship. In the article, I present the civic activity of women subjected to a quantitative analysis against the background of a specific factor, which is religion (specifically Christianity). The article presents the civic activity of women, manifested by street protests undertaken after the tightening of the abortion law in Poland in 2020. The research material was collected using CAWI (Computer Assisted Web Interview); the sample size was N = 585. The obtained empirical data confirm that religion determines views on abortion and motives for participation in protests.